2011
DOI: 10.1371/annotation/5247af81-4595-44b7-9c3f-2e45ad85abfa
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Novel Murine Infection Models Provide Deep Insights into the “Ménage à Trois” of Campylobacter jejuni, Microbiota and Host Innate Immunity

Abstract: Background: Although Campylobacter jejuni-infections have a high prevalence worldwide and represent a significant socioeconomic burden, it is still not well understood how C. jejuni causes intestinal inflammation. Detailed investigation of C. jejuni-mediated intestinal immunopathology is hampered by the lack of appropriate vertebrate models. In particular, mice display colonization resistance against this pathogen. Methodology/Principal Findings:To overcome these limitations we developed a novel C. jejuni-infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(108 citation statements)
references
References 35 publications
6
102
0
Order By: Relevance
“…This can be attributed to the fact that mice are approximately 10,000-fold less responsive to Toll-like receptor (TLR)-4 ligands, mainly LOS and LPS [44] (Figure 3). Furthermore, the gastrointestinal microbiota of conventional mice mediates a strong colonization resistance (CR) to C. jejuni [45][46][47]. In line with other investigators, we have recently shown that conventional mice bred in our specific pathogen-free (SPF) facilities are protected from stable gastrointestinal C. jejuni colonization even upon peroral infection with high doses.…”
Section: Figuresupporting
confidence: 76%
See 2 more Smart Citations
“…This can be attributed to the fact that mice are approximately 10,000-fold less responsive to Toll-like receptor (TLR)-4 ligands, mainly LOS and LPS [44] (Figure 3). Furthermore, the gastrointestinal microbiota of conventional mice mediates a strong colonization resistance (CR) to C. jejuni [45][46][47]. In line with other investigators, we have recently shown that conventional mice bred in our specific pathogen-free (SPF) facilities are protected from stable gastrointestinal C. jejuni colonization even upon peroral infection with high doses.…”
Section: Figuresupporting
confidence: 76%
“…In line with other investigators, we have recently shown that conventional mice bred in our specific pathogen-free (SPF) facilities are protected from stable gastrointestinal C. jejuni colonization even upon peroral infection with high doses. Upon modifying the murine gut microbiota (i.e., its virtual depletion) following broad-spectrum antibiotic treatment, and also upon re-association with human as opposed to murine gut microbiota by fecal microbiota transplantation, these mice can be effectively colonized by the pathogen upon peroral challenge and display typical histopathologic pro-inflammatory features of campylobacteriosis in their intestines [46][47][48][49], whereas the classic symptoms such as abdominal cramps, watery, or bloody diarrhea seen in infected humans were missing in conventional wildtype mice without genetic manipulations [46] (Figure 4).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotic-treated and gnotobiotic mice display increased colonization and gastrointestinal inflammation after C. jejuni inoculation (Chang and Miller, 2006;Stahl et al, 2014;O'Loughlin et al, 2015), with a potential protective role for Enterococcus faecalis (O'Loughlin et al, 2015). Furthermore, a considerably decreased C. jejuni clearance time is observed in mice that receive antibiotics and gavage with murine microbiota compared to human microbiota-receiving mice and gnotobiotic mice, that showed a more pro-inflammatory immune response (Bereswill et al, 2011).…”
Section: Role Of the Gut Microbiota In Disease Symptoms And Pathogenesismentioning
confidence: 99%
“…The microbiota has been shown to be involved in numerous physiological processes, including vitamin synthesis (LeBlanc et al, 2013), food digestion (Hooper et al, 2002), fat metabolism (Backhed et al, 2004), intestinal angiogenesis (Stappenbeck et al, 2002), enteric nerve function (Husebye et al, 1994), protection from pathogens (Sekirov et al, 2008; Bereswill et al, 2011), and immune system development (Cebra, 1999). Moreover, perturbations of the complex host resident intestinal ecologic system, termed dysbiosis, have been linked to a wide range of pathological conditions including intestinal disorders such as inflammatory bowel diseases (IBD; Baumgart and Carding, 2007), irritable bowel syndrome (IBS; Carroll et al, 2010), and coeliac disease (De Palma et al, 2010), as well as extra-intestinal pathologies such as allergy and asthma (Noverr and Huffnagle, 2004), arthritis (Taurog et al, 1994), type 1 diabetes mellitus (Wen et al, 2008), obesity (Backhed et al, 2007), multiple sclerosis (Ochoa-Reparaz et al, 2009), and distinct cardiovascular diseases (Serino et al, 2014).…”
Section: Introductionmentioning
confidence: 99%